Analysis of body mass index, weight loss and progression of idiopathic pulmonary fibrosis - Jouneau, Stéphane; Crestani, Bruno; Thibault, Ronan; Lederlin, Mathieu; Vernhet, Laurent; Valenzuela, Claudia; Wijsenbeek, Marlies; Kreuter, Michael; Stansen, Wibke; Quaresma, Manuel; Cottin, Vincent (Respiratory research, 2020)
Nintedanib is an approved therapy for idiopathic pulmonary fibrosis (IPF). Some patients treated with nintedanib experience weight loss. Exploratory data suggest that low body mass index or weight loss are associated with worse outcomes in patients with IPF. We investigated whether BMI at baseline or weight loss over 52 weeks was associated with FVC decline, or influenced the effect of nintedanib, in patients with IPF.
Gesehen am 27.01.2021